Antifungal Activity Against Botrytis Cinerea of 2,6-Dimethoxy-4-(Phenylimino)Cyclohexa-2,5-Dienone Derivatives - Vasquez-Guzman, C; Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Santander-Meyer, R; Castro-Valenzuela, P; Castro-Valenzuela, P; Navarro-Gajardo, F; Navarro-Gajardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
In this work the enzyme laccase from Trametes versicolor was used to synthetize 2,6-dimethoxy-4-(phenylimino)cyclohexa-2,5-dienone derivatives. Ten products with different substitutions in the aromatic ring were synthetized and characterized using1H- and13C-NMR and mass spectrometry. The 3,5-dichlorinated compound showed highest antifungal activity against the phytopathogen Botrytis cinerea, while the p-methoxylated compound had the lowest activity; however, the antifungal activity of the products was higher than the activity of the substrates of the reactions. Finally, the results suggested that these compounds produced damage in the fungal cell wall. © 2019 by the authors.